Awareness And Perceptions Towards Eye Donation Among Undergraduate Medical And Allied Health Sciences Students In An University Teaching Hospital In Chennai (Journal of Pharmaceutical Negative Results, 2022)
Aim: To assess the awareness and attitudes towards eye donation in an university hospital students (medical and allied health sciences)Methodology: A cross sectional descriptive study was done after obtaining Institutional ethics approval. The questionnaire consisted of majority of questions from a pre validated questionnaire on knowledge and awareness regarding eye donation and a few open-ended questions. The questionnaire was circulated as a google form among medical and allied health science undergraduate students of university teaching hospital in Tamil Nadu. The results were analysed using Microsoft excel and SPSS software and appropriate statistical tests were performed.Results: In all of the 327 participants who responded, 94.5% of undergraduate medical and allied health science (AHS) students are aware of eye donation. There was a statistical significance with regard to the level of awareness among medical versus AHS students. Among the medical undergraduate students 70% were willing to donate eye as compared to 59% of the AHS students. Barriers to eye donation include social and religious reasons and lack of awareness. In addition, there is inadequate awareness regarding which part of the eye is used, in spite of the national programs such as VISION 2020 and Right to Sight and other initiatives on eye donation. An overwhelming 96% of the participants feel that more efforts are required to create awareness regarding eye donation.Conclusion: In order to strengthen the national programme initiatives a structured awareness regarding eye donation must be included in the teaching programme of all health care professional students and target specific measures to overcome the barriers..